Teams promise but do not deliver - Nielsen, Kirby; Bhattacharya, Puja; Kagel, John H.; Sengupta, Arjun (Games and economic behavior, 2019)
Individuals and two-person teams play a hidden-action trust game with pre-play communication. We replicate previous results for individuals that non-binding promises increase cooperation rates, but this does not extend to teams. While teams promise to cooperate at the same rate as individuals, they consistently renege on those promises. Additional treatments begin to explore the basis for team behavior. We rule out explanations hypothesizing that concern for partner's payoff drives team outcomes, as absent within-team communication, promise fulfillment rates increase compared to individuals. Rather, the results are consistent with the idea that communication between teammates provides support for self-serving behavior.